2000
DOI: 10.1590/s0104-11692000000100016
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos gerais da sexualidade dos portadores de tuberculose pulmonar atendidos em unidades básicas de saúde de Ribeirão Preto-SP

Abstract: This descriptive study was carried out in order to identify and analysing the knowledge that the patients with pulmonary tuberculosis have about the disease and the experiences which they have passed through; to identify some aspects related to their sexuality's changing after acquiring the pulmonary tuberculosis and characterizing the living experiences toward their family, the friends'/relatives' reactions and the emerging feelings. Fifty sexually active patients were interviewed. The results showed that 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
6

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 3 publications
3
5
0
6
Order By: Relevance
“…The representation o tuberculosis presentation as a disease with difficult treatment is in agreement with another study (8) . Authors reported that taking the medicine will depend on how people control or articulate their bodies and on their perception of a satisfactory body response to unpleasant sensations.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The representation o tuberculosis presentation as a disease with difficult treatment is in agreement with another study (8) . Authors reported that taking the medicine will depend on how people control or articulate their bodies and on their perception of a satisfactory body response to unpleasant sensations.…”
Section: Discussionsupporting
confidence: 89%
“…This prejudice is related to the contagion idea, which is also demonstrated by another study which shows that individuals with pulmonary tuberculosis suffer with the disease, not only due to its clinical manifestations, but also to the possibility of experiencing prejudices and being rejected in their social relationships (8) .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…These papers show a concern with aspects of sexuality that go beyond a biologistic view, however, a physiopathological approach to diseases is the dominant view, while sexuality is reduced to the sexual act per se (25)(26)(27)(28) . These two papers do not present a theoretical discussion and in some there is no reference to the concept of sexuality that guides the view of researchers.…”
Section: Sexuality and Chronic-degenerative Diseases And/or Surgeriesmentioning
confidence: 99%
“…These two papers do not present a theoretical discussion and in some there is no reference to the concept of sexuality that guides the view of researchers. Even though sexuality is one of the key words used, it is not a central issue in the studies described by these two papers (25)(26) .…”
Section: Sexuality and Chronic-degenerative Diseases And/or Surgeriesmentioning
confidence: 99%